Thermoplastic resin composition and molded article thereof

By using a thermoplastic resin composition of a specific proportion of vinyl-based copolymer, rubber-reinforced graft copolymer and polyamide elastomer, the existing resins have been solved, and the existing resins have been excellent in sheet molding, and the productivity, transparency, rigidity and heat resistance of sheet molding have been significantly improved.

CN119744283APending Publication Date: 2025-04-01大科能宇菱通株式会社
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380060790.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-08-28
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing rubber-reinforced styrene resins have low productivity, poor transparency, insufficient chemical resistance in sheet molding, and it is difficult to improve sheet molding, chemical resistance, transparency and rigidity at the same time.

Method used

A thermoplastic resin composition using a specific proportion of vinyl-based copolymer, rubber-reinforced graft copolymer and polyamide elastomer is formed by copolymerization and grafting reactions to form a resin with excellent molding properties.

Benefits of technology

Excellent productivity, transparency, rigidity and heat resistance of tablet forming have been significantly improved, and the resistance to chemicals has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005277604240000291
    Figure BDA0005277604240000291
  • Figure BDA0005277604240000301
    Figure BDA0005277604240000301
  • Figure BDA0005277604240000311
    Figure BDA0005277604240000311
Patent Text Reader

Abstract

A thermoplastic resin composition containing: a vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth) acrylic acid ester monomer (a2); a rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing, in the presence of a rubbery polymer (r), a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth) acrylate monomer (b2), and a vinyl cyanide monomer (b3); the present invention relates to a thermoplastic elastomer composition containing a vinyl copolymer (A) and a polyamide elastomer (C), the vinyl copolymer (A) including a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth) acrylate monomer (a2), and a vinyl cyanide monomer (a3), the vinyl copolymer (A1) having a weight-average molecular weight of 50,000-300,000; the thermoplastic resin composition contains 60-92 parts by mass of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) in total and 8-40 parts by mass of the polyamide elastomer (C) per 100 parts by mass of the total of the vinyl copolymer (A), the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoplastic resin composition comprising a vinyl copolymer, a rubber-reinforced graft copolymer and a polyamide elastomer. According to the thermoplastic resin composition of the present invention, a molded product having excellent productivity in sheet molding, excellent chemical resistance, transparency and rigidity can be obtained. The present invention also relates to a molded product obtained by molding the thermoplastic resin composition. Background Art

[0002] Rubber-reinforced styrene resins obtained by graft copolymerizing aromatic vinyl compounds such as styrene and α-methylstyrene and cyanide vinyl compounds such as acrylonitrile and methacrylonitrile onto rubber polymers such as diene rubbers have excellent mechanical strength such as impact resistance and rigidity, moldability and cost-effectiveness. Therefore, rubber-reinforced styrene resins are widely used in home appliances, communication-related equipment, transport containers, general sundries, and medical-related equipment.

[0003] In such a wide range of applications, rubber-reinforced styrene resins are sometimes used as films or sheets. In this case, from the perspective of productivity, resins with relatively low fluidity in sheet or film molding (hereinafter collectively referred to as "sheet molding") are preferred. Therefore, in order to reduce fluidity, the ratio of the rubber polymer in the rubber-reinforced styrene resin is designed to be higher.

[0004] On the other hand, rubber-reinforced styrene resins are generally opaque, but depending on the product, transparency like polymethyl methacrylate and polycarbonate resins is sometimes required. In response to such a requirement, it is known that transparency can be obtained in rubber-reinforced styrene resins by adjusting the composition ratio of each component constituting the resin, as described in Patent Document 1, for example.

[0005] As an example of the use of transparent sheet materials, there can be cited conveying equipment and transport containers for precision parts. In such uses, the resin may deteriorate due to the adhesion of cleaning agents used for precision parts, which may cause a decrease in transparency, cracks, and breakage. Therefore, in order to prevent such problems, chemical resistance is also required.

[0006] However, conventionally provided transparent materials of rubber-reinforced styrene resins have improved transparency by increasing the ratio of (meth)acrylate in the composition, as described in Patent Documents 2 and 3. As a result of increasing the ratio of (meth)acrylate, chemical resistance to cleaning agents such as isopropyl alcohol is insufficient.

[0007] Patent Document 3 proposes the following thermoplastic resin composition with the aim of improving adhesion, impact resistance, antistatic properties, and color tone due to organic solvents instead of sheet moldability and chemical resistance.

[0008] A thermoplastic resin composition, which is a thermoplastic resin composition obtained by mixing a vinyl copolymer (A), a graft copolymer (B) and a polyamide elastomer (C), wherein the vinyl copolymer (A) is obtained by copolymerizing a vinyl monomer mixture (a) containing at least 5 to 40% by weight of an aromatic vinyl monomer (a1), 30 to 80% by weight of a (meth)acrylate monomer (a2) and 10 to 50% by weight of a cyanide vinyl monomer (a3), and the graft copolymer (B) is obtained by copolymerizing at least 5 to 40% by weight of an aromatic vinyl monomer (a1), 30 to 80% by weight of a (meth)acrylate monomer (a2) and 10 to 50% by weight of a cyanide vinyl monomer (a3) ​​in the presence of a rubber polymer (r). The thermoplastic resin composition is formed by graft copolymerizing a vinyl monomer mixture (mb) of 10 to 30 mass % of a vinyl monomer (b1), 30 to 80 mass % of a (meth)acrylate monomer (b2) and 1 to 10 mass % of a cyanide vinyl monomer (b3), wherein the thermoplastic resin composition is formed by mixing 40 to 90 mass parts of the vinyl copolymer (A), 10 to 60 mass parts of the graft copolymer (B) and 3 mass parts or more of the polyamide elastomer (C) relative to 100 mass parts of the total of the vinyl copolymer (A) and the graft copolymer (B).

[0009] However, Patent Document 3 does not have the problem of improving the productivity of sheet molding and chemical resistance. In addition, the molecular weight of the vinyl copolymer (A) in the thermoplastic resin composition of Patent Document 3 is small, and the proportion of the rubber-reinforced graft copolymer (B) in the resin component is also small, and the sheet moldability that is the problem of the present invention cannot be obtained.

[0010] In addition, Patent Document 4 discloses a technique for regulating the acrylonitrile content in the acetone-soluble component of a thermoplastic resin composition. However, according to this technique, when an attempt is made to improve chemical resistance or impart antistatic properties by blending a polyamide elastomer, there is a problem that transparency is greatly impaired.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Laid-Open No. 4-180907

[0014] Patent Document 2: Japanese Patent Application Publication No. 2003-147152

[0015] Patent Document 3: Japanese Patent Application Publication No. 2017-145365

[0016] Patent Document 4: International Publication No. 2016 / 104259 Summary of the invention

[0017] Problems to be solved by the invention

[0018] An object of the present invention is to provide a thermoplastic resin composition which can produce a molded product having excellent productivity in sheet molding and excellent chemical resistance, transparency, rigidity and heat resistance.

[0019] Means for solving problems

[0020] The present inventors have found that a thermoplastic resin composition containing a specific vinyl copolymer, a rubber-reinforced graft copolymer, and a polyamide elastomer in a predetermined ratio can solve the above-mentioned problems.

[0021] That is, the gist of the present invention is as follows.

[0022] [1] A thermoplastic resin composition, comprising:

[0023] A vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2);

[0024] A rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r); and

[0025] Polyamide elastomer (C),

[0026] in,

[0027] The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 50,000 to 300,000.

[0028] The thermoplastic resin composition contains a total of 60 to 92 parts by mass of the vinyl copolymer (A) and the rubber reinforced graft copolymer (B), and 8 to 40 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B) and the polyamide elastomer (C).

[0029] [2] The thermoplastic resin composition as described in [1], which contains 20 to 65 parts by mass of the vinyl copolymer (A), 5 to 72 parts by mass of the rubber reinforced graft copolymer (B), and 8 to 30 parts by mass of the polyamide elastomer (C), based on 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B), and the polyamide elastomer (C).

[0030] [3] The thermoplastic resin composition according to [1] or [2], comprising:

[0031] A vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2);

[0032] A rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r); and

[0033] Polyamide elastomer (C),

[0034] in,

[0035] The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 100,000 to 250,000.

[0036] The thermoplastic resin composition contains 20 to 40 parts by mass of the vinyl copolymer (A), 47 to 65 parts by mass of the rubber reinforced graft copolymer (B), and 8 to 13 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B), and the polyamide elastomer (C), and contains 35 parts by mass or less of the vinyl copolymer (A1).

[0037] [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the vinyl copolymer (A) further comprises a vinyl copolymer (A2), which is obtained by copolymerizing a vinyl monomer mixture (ma2) comprising an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a maleimide monomer (a4), and has a weight average molecular weight of 100,000 to 250,000,

[0038] The thermoplastic resin composition contains 20 parts by mass or less of the vinyl copolymer (A2) based on 100 parts by mass of the total of the vinyl copolymer (A), the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C).

[0039] [5] The thermoplastic resin composition according to any one of [1] to [4], wherein the refractive index of the vinyl copolymer (A), the acetone-soluble component of the rubber-reinforced graft copolymer (B), and the polyamide elastomer (C) is in the range of 1.505 to 1.520,

[0040] The difference in refractive index between these components is 0.03 or less.

[0041] [6] The thermoplastic resin composition according to any one of [1] to [5], wherein the content of the vinyl cyanide monomer component in 100% by mass of the acetone-soluble component of the thermoplastic resin composition is 0.5 to 10% by mass.

[0042] [7] A molded article comprising the thermoplastic resin composition according to any one of [1] to [6].

[0043] [8] The molded article according to [7], which is a sheet-like molded article.

[0044] Effects of the Invention

[0045] According to the thermoplastic resin composition of the present invention, it is possible to provide a molded product, particularly a sheet-shaped molded product, which is excellent in productivity in sheet molding and excellent in chemical resistance, transparency, rigidity and heat resistance. DETAILED DESCRIPTION

[0046] Embodiments of the present invention will be described in detail below.

[0047] In this specification, the "molded article" refers to a molded article obtained by molding a thermoplastic resin composition.

[0048] In this specification, "(co)polymer" and "(co)polymer" refer to "homopolymer" and / or "copolymer", and "homopolymer" and / or "copolymer", respectively. "(Meth)acrylic acid" and "(meth)acrylate" refer to "acrylic acid" and / or "methacrylic acid", and "acrylate" and / or "methacrylate", respectively.

[0049] Hereinafter, the "productivity of sheet molding" may be simply referred to as "sheet moldability".

[0050] [Thermoplastic resin composition]

[0051] The thermoplastic resin composition of the present invention comprises:

[0052] A vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2);

[0053] A rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r); and

[0054] Polyamide elastomer (C),

[0055] It is characterized in that

[0056] The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 50,000 to 300,000.

[0057] The thermoplastic resin composition contains a total of 60 to 92 parts by mass of the vinyl copolymer (A) and the rubber reinforced graft copolymer (B), and 8 to 40 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B) and the polyamide elastomer (C).

[0058] Hereinafter, the rubber-reinforced graft copolymer (B) may be simply referred to as "graft copolymer (B)".

[0059] The thermoplastic resin composition of the present invention comprises a vinyl copolymer (A) containing the above-mentioned vinyl copolymer (A1), a rubber-reinforced graft copolymer (B) and a polyamide elastomer (C) in a prescribed ratio, and the weight average molecular weight of the vinyl copolymer (A1) is 50,000 to 300,000, so that the transparency, rigidity and heat resistance of the obtained molded product can be improved. In addition, by containing the rubber-reinforced graft copolymer (B), the chemical resistance of the molded product and the fluidity suitable for sheet molding can be improved. Furthermore, by containing the polyamide elastomer (C), the chemical resistance of the molded product can be improved.

[0060] <Vinyl Copolymer (A)>

[0061] The vinyl copolymer (A) is obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2). The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 50,000 to 300,000.

[0062] The vinyl copolymer (A) preferably contains a vinyl copolymer (A1) and a vinyl copolymer (A2) in a manner to achieve an appropriate content as described later, wherein the vinyl copolymer (A2) is obtained by copolymerizing a vinyl monomer mixture (ma2) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a maleimide monomer (a4), and has a weight average molecular weight of 100,000 to 250,000.

[0063] That is, the vinyl copolymer (A) may consist of the vinyl copolymer (A1) alone and not contain the vinyl copolymer (A2), or may contain the vinyl copolymer (A1) and the vinyl copolymer (A2).

[0064] In the present invention, the vinyl copolymer (A1) may be used alone or in combination of two or more different monomer compositions, physical properties, etc. The vinyl copolymer (A2) may be used alone or in combination of two or more different monomer compositions, physical properties, etc.

[0065] (vinyl copolymer (A1))

[0066] The vinyl copolymer (A1) is obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3). The vinyl copolymer (A1) is preferably obtained by copolymerizing a vinyl monomer mixture (ma1) containing 5 to 40% by mass of an aromatic vinyl monomer (a1), 30 to 85% by mass of a (meth)acrylate monomer (a2) and 2 to 30% by mass of a cyanide vinyl monomer (a3) ​​according to a conventional method. The vinyl monomer mixture (ma1) may further contain other vinyl copolymers that can copolymerize with the aromatic vinyl monomer (a1), the (meth)acrylate monomer (a2) and the cyanide vinyl monomer (a3).

[0067] As the aromatic vinyl monomer (a1), for example, styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, o-methylstyrene, vinyltoluene, tert-butylstyrene, etc. can be mentioned. One of them can be used alone, or two or more of them can be used in combination. Among them, styrene is preferred from the aspect of improving the moldability of the thermoplastic resin composition and the rigidity of the obtained molded article.

[0068] In the total 100% by mass of the vinyl monomer mixture (ma1), the content of the aromatic vinyl monomer (a1) in the vinyl monomer mixture (ma1) is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 19% by mass or more. If the content of the aromatic vinyl monomer (a1) is above the above lower limit, the moldability of the thermoplastic resin composition (A1) and the rigidity of the obtained molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (ma1), the content of the aromatic vinyl monomer (a1) in the vinyl monomer mixture (ma1) is preferably 40% by mass or less, more preferably 30% by mass or less, and further preferably 27% by mass or less. If the content of the aromatic vinyl monomer (a1) is below the above upper limit, the impact resistance and transparency of the obtained molded article can be further improved.

[0069] The (meth)acrylate monomer (a2) is not particularly limited, but preferably is an ester of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid. The ester of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid may further have a substituent such as a hydroxyl group or a halogen group. As the ester of an alcohol having 1 to 6 carbon atoms and acrylic acid or methacrylic acid, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, chloromethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, etc. may be mentioned. One of them may be used alone, or two or more of them may be used in combination. Among them, methyl (meth)acrylate is preferred from the aspect of improving the transparency of the obtained molded article.

[0070] In the total 100% by mass of the vinyl monomer mixture (ma1), the content of the (meth) acrylate monomer (a2) in the vinyl monomer mixture (ma1) is preferably 30% by mass or more, more preferably 50% by mass or more, and further preferably 65% ​​by mass or more. If the content of the (meth) acrylate monomer (a2) is above the above lower limit, the transparency of the obtained molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (ma1), the content of the (meth) acrylate monomer (a2) in the vinyl monomer mixture (ma1) is preferably 85% by mass or less, more preferably 80% by mass or less, and further preferably 75% by mass or less. If the content of the (meth) acrylate monomer (a2) is below the above upper limit, the chemical resistance and transparency of the obtained molded article can be further improved.

[0071] Examples of the vinyl cyanide monomer (a3) ​​include acrylonitrile, methacrylonitrile, ethacrylonitrile, etc. These monomers may be used alone or in combination of two or more. Of these, acrylonitrile is preferred from the perspective of further improving the chemical resistance of the resulting molded article.

[0072] In the total 100% by mass of the vinyl monomer mixture (ma1), the content of the cyanide vinyl monomer (a3) ​​in the vinyl monomer mixture (ma1) is preferably 2 to 30% by mass. If the content of the cyanide vinyl monomer (a3) ​​is less than 2% by mass, there is a tendency for chemical resistance to decrease. Therefore, the content of the cyanide vinyl monomer (a3) ​​is preferably 2% by mass or more, more preferably 5% by mass or more, and further preferably 6% by mass or more. On the other hand, if the content of the cyanide vinyl monomer (a3) ​​exceeds 30% by mass, there is a tendency for the yellowness (YI) of the obtained molded article to increase and the hue to decrease. Therefore, the content of the cyanide vinyl monomer (a3) ​​in the vinyl monomer mixture (ma1) is preferably 30% by mass or less, more preferably 20% by mass or less, further preferably 10% by mass or less, particularly preferably 9% by mass or less, and most preferably 8% by mass or less.

[0073] Other vinyl copolymers that can be copolymerized with them are not particularly limited as long as they are vinyl monomers other than the above-mentioned aromatic vinyl monomer (a1), (methyl) acrylate monomer (a2), and cyanide vinyl monomer (a3) ​​and do not impair the effect of the present invention. Specifically, unsaturated fatty acids, acrylamide monomers, maleimide monomers, etc. can be cited. They can be used alone or in combination of two or more.

[0074] Examples of the unsaturated fatty acid include itaconic acid, maleic acid, fumaric acid, crotonic acid, acrylic acid, and methacrylic acid.

[0075] Examples of the acrylamide monomer include acrylamide, methacrylamide, and N-methylacrylamide.

[0076] Examples of the maleimide monomer include N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, N-butylmaleimide, N-hexylmaleimide, N-octylmaleimide, N-dodecylmaleimide, N-cyclohexylmaleimide, and N-phenylmaleimide.

[0077] When the vinyl monomer mixture (ma1) contains these other vinyl copolymers, the content of the other vinyl copolymers in 100% by mass of the vinyl monomer mixture (ma1) is preferably 10% by mass or less, more preferably 0 to 5% by mass. If the content of the other vinyl copolymers is below the above upper limit, the effect of using the aromatic vinyl monomer (a1), the (meth) acrylate monomer (a2) and the cyanide vinyl monomer (a3) ​​in a prescribed ratio can be effectively obtained.

[0078] (vinyl copolymer (A2))

[0079] The vinyl copolymer (A2) is obtained by copolymerizing a vinyl monomer mixture (ma2) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a maleimide monomer (a4). The vinyl copolymer (A2) is preferably obtained by copolymerizing a vinyl monomer mixture (ma2) containing 2 to 30% by mass of an aromatic vinyl monomer (a1), 30 to 80% by mass of a (meth)acrylate monomer (a2) and 10 to 50% by mass of a maleimide monomer (a4) according to a conventional method. The vinyl monomer mixture (ma2) may further contain other monomers that can copolymerize with the aromatic vinyl monomer (a1), the (meth)acrylate monomer (a2) and the maleimide monomer (a4).

[0080] As the aromatic vinyl monomer (a1), there may be mentioned those exemplified as the aromatic vinyl monomer (a1) used in the vinyl copolymer (A1). As the aromatic vinyl monomer (a1), styrene is preferred.

[0081] In the total 100% by mass of the vinyl monomer mixture (ma2), the content of the aromatic vinyl monomer (a1) in the vinyl monomer mixture (ma2) is preferably more than 2% by mass, more preferably more than 5% by mass. If the content of the aromatic vinyl monomer (a1) is more than the above lower limit, the moldability of the thermoplastic resin composition and the rigidity of the resulting molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (ma2), the content of the aromatic vinyl monomer (a1) in the vinyl monomer mixture (ma2) is preferably less than 30% by mass, more preferably less than 20% by mass, and further preferably less than 15% by mass. If the content of the aromatic vinyl monomer (a1) is less than the above upper limit, the impact resistance and transparency of the resulting molded article can be further improved.

[0082] Examples of the (meth)acrylate monomer (a2) include those exemplified as the (meth)acrylate monomer (a2) used in the vinyl copolymer (A1). As the (meth)acrylate monomer (a2), methyl (meth)acrylate is preferred.

[0083] In the total 100% by mass of the vinyl monomer mixture (ma2), the content of the (meth) acrylate monomer (a2) in the vinyl monomer mixture (ma2) is preferably 30% by mass or more, more preferably 50% by mass or more, and further preferably 55% by mass or more. If the content of the (meth) acrylate monomer (a2) is above the above lower limit, the transparency of the obtained molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (ma2), the content of the (meth) acrylate monomer (a2) in the vinyl monomer mixture (ma2) is preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less. If the content of the (meth) acrylate monomer (a2) is below the above upper limit, the chemical resistance of the obtained molded article can be further improved.

[0084] The maleimide monomer (a4) includes those exemplified as maleimide monomers of other vinyl copolymers used as necessary in the vinyl copolymer (A1). As the maleimide monomer (a4), N-phenylmaleimide is preferred.

[0085] In the total 100 mass % of the vinyl monomer mixture (ma2), the content of the maleimide monomer (a4) in the vinyl monomer mixture (ma2) is preferably 10 to 50 mass %. If the content of the maleimide monomer (a4) is less than 10 mass %, there is a tendency for heat resistance to decrease. Therefore, the content of the maleimide monomer (a4) is preferably 10 mass % or more, more preferably 15 mass parts or more. If the content of the maleimide monomer (a4) exceeds 50 mass %, there is a tendency for the fluidity of the thermoplastic resin composition to decrease. Therefore, the content of the maleimide monomer (a4) is preferably 50 mass % or less, more preferably 35 mass % or less, and further preferably 30 mass % or less.

[0086] Other vinyl copolymers copolymerizable with these are not particularly limited as long as they are vinyl monomers other than the above-mentioned aromatic vinyl monomers (a1), (meth)acrylate monomers (a2), and maleimide monomers (a4) and do not impair the effects of the present invention. Specifically, cyanide vinyl monomers, unsaturated fatty acids, acrylamide monomers, etc. can be cited.

[0087] Examples of the vinyl cyanide monomer include those exemplified as the vinyl cyanide monomer (a3) ​​used in the vinyl copolymer (A1).

[0088] As the unsaturated fatty acid and acrylamide-based monomer, those exemplified as other vinyl-based copolymers used in the vinyl-based copolymer (A1) can be mentioned.

[0089] When the vinyl monomer mixture (ma2) contains these other vinyl copolymers, the content of the other vinyl copolymers in 100% by mass of the vinyl monomer mixture (ma2) is preferably 10% by mass or less, more preferably 0 to 5% by mass. If the content of the other vinyl copolymers is below the above upper limit, the effect of using the aromatic vinyl monomer (a1), the (meth) acrylate monomer (a2) and the maleimide monomer (a4) in a prescribed ratio can be effectively obtained.

[0090] (Physical Properties of Vinyl Copolymer (A))

[0091] In the present invention, the weight average molecular weight (Mw) of the vinyl copolymer (A1) is 50,000 to 300,000, preferably 100,000 to 250,000. The weight average molecular weight (Mw) of the vinyl copolymer (A2) is preferably 100,000 to 250,000. If the weight average molecular weight of each of the vinyl copolymer (A1) and the vinyl copolymer (A2) is above the above lower limit, the obtained thermoplastic resin composition becomes low fluidity and excellent sheet formability. If the weight average molecular weight of each of the vinyl copolymer (A1) and the vinyl copolymer (A2) exceeds the above upper limit, there is a tendency that the flowability becomes too low and the sheet formability is poor.

[0092] The vinyl copolymer (A1) having a weight average molecular weight (Mw) of 50,000 to 300,000 and the vinyl copolymer (A2) having a weight average molecular weight (Mw) of 100,000 to 250,000 can be easily produced, for example, by using an initiator and a chain transfer agent described below and by setting the polymerization temperature within the preferred range described below.

[0093] The refractive index of the vinyl copolymer (A) is preferably 1.505 to 1.520, more preferably 1.509 to 1.519, and further preferably 1.510 to 1.517. If the refractive index of the vinyl copolymer (A) is within the above range, the refractive index difference with the rubber-reinforced graft copolymer (B) described later can be reduced, and the transparency of the obtained molded article can be excellent.

[0094] From the perspective of transparency of the resulting molded article, the difference between the refractive index of the vinyl copolymer (A), the refractive index of the acetone-soluble component of the rubber-reinforced graft copolymer (B) described later, and the refractive index of the polyamide elastomer (C) is preferably 0.03 or less, particularly preferably 0.01 or less.

[0095] The refractive index of the vinyl copolymer (A) mainly depends on the composition of the vinyl monomer as a raw material. Therefore, the refractive index can be adjusted to a desired range by appropriately selecting the type and composition ratio of the vinyl monomer.

[0096] The weight average molecular weight (Mw) and refractive index of the vinyl copolymer (A) are measured by the method described in the section of Examples described later.

[0097] (Method for producing vinyl copolymer (A))

[0098] The method for producing the vinyl copolymer (A) is not particularly limited, and the above-mentioned vinyl monomer mixture (ma) (vinyl monomer mixture (ma1) or vinyl monomer mixture (ma2)) can be used as a raw material and produced by a known polymerization method. From the perspective of improving the moldability, transparency and color stability of the obtained thermoplastic resin composition, it is preferred to use a continuous bulk polymerization method or a continuous solution polymerization method.

[0099] As a method for producing the vinyl copolymer (A) by continuous bulk polymerization or continuous solution polymerization, any method may be adopted, for example, a method in which a vinyl monomer mixture (ma) is polymerized in a polymerization tank and then subjected to monomer stripping (desolventization and devolatilization).

[0100] <Rubber-reinforced graft copolymer (B)>

[0101] The graft copolymer (B) is obtained by graft copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a vinyl cyanide monomer (b3) in the presence of a rubber polymer (r).

[0102] The graft copolymer (B) is preferably obtained by graft copolymerizing a vinyl monomer mixture (mb) containing 5 to 40% by mass of an aromatic vinyl monomer (b1), 30 to 85% by mass of a (meth)acrylate monomer (b2) and 2 to 30% by mass of a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r). The vinyl monomer mixture (mb) may further contain other vinyl copolymers copolymerizable with the aromatic vinyl monomer (b1), the (meth)acrylate monomer (b2) and the cyanide vinyl monomer (b3).

[0103] Examples of the rubber polymer (r) include polybutadiene, polyisoprene, butyl rubber, styrene-butadiene copolymer (preferably 5 to 60% by mass of styrene content), styrene-isoprene copolymer, acrylonitrile-butadiene copolymer, ethylene-α-olefin copolymer, ethylene-α-olefin-polyene copolymer, silicone rubber, acrylic rubber, butadiene-(meth)acrylate copolymer, polyisoprene, styrene-butadiene block copolymer, styrene-isoprene block copolymer, hydrogenated styrene-butadiene block copolymer, hydrogenated butadiene polymer, ethylene ionomer, etc. The styrene-butadiene block copolymer and styrene-isoprene block copolymer include block copolymers having AB type, ABA type, tapered type, or radial (radialteleblock) type structures. In addition to the hydrogenated products of the above block copolymers, the hydrogenated butadiene polymers also include hydrogenated products of polystyrene blocks and blocks of styrene-butadiene random copolymers; and hydrogenated products of polymers composed of blocks having a 1,2-vinyl bond content of 20% by mass or less in polybutadiene and blocks having a 1,2-vinyl bond content of more than 20% by mass.

[0104] Among them, polybutadiene and ethylene-α-olefin copolymers are often used as the rubber polymer (r).

[0105] These rubber polymers (r) may be used alone or in combination of two or more.

[0106] The amount of the rubber polymer (r) used is preferably 20 to 80 parts by mass relative to the total amount of 100 parts by mass of the rubber polymer (r) and the vinyl monomer mixture (mb) described later constituting the rubber reinforced graft copolymer (B). If the amount of the rubber polymer (r) used is 20 parts by mass or more, the impact resistance of the resulting molded article can be further improved. The content of the rubber polymer (r) is more preferably 35 parts by mass or more. If the content of the rubber polymer (r) is 80 parts by mass or less, the moldability of the thermoplastic resin composition can be further improved. The content of the rubber polymer (r) is more preferably 60 parts by mass or less.

[0107] The volume average particle size of the rubber polymer (r) is not particularly limited, but is preferably 80 nm or more, more preferably 150 nm or more, from the perspective of further improving the impact resistance of the obtained molded article. From the perspective of improving the transparency of the obtained molded article, the volume average particle size of the rubber polymer (r) is preferably 500 nm or less, more preferably 350 nm or less, and further preferably 300 nm or less.

[0108] The volume average particle diameter of the rubber polymer (r) and the rubber-reinforced graft copolymer (B) described later is measured by the method described in the section of Examples described later.

[0109] As the aromatic vinyl monomer (b1), there may be mentioned those exemplified as the aromatic vinyl monomer (a1). As the aromatic vinyl monomer (b1), styrene is preferred.

[0110] In the total 100% by mass of the vinyl monomer mixture (mb), the content of the aromatic vinyl monomer (b1) in the vinyl monomer mixture (mb) is preferably 5% by mass or more, more preferably 10% by mass or more. If the content of the aromatic vinyl monomer (b1) is above the above lower limit, the moldability of the thermoplastic resin composition and the rigidity of the resulting molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (mb), the content of the aromatic vinyl monomer (b1) in the vinyl monomer mixture (mb) is preferably 40% by mass or less, more preferably 30% by mass or less. If the content of the aromatic vinyl monomer (b1) is below the above upper limit, the impact resistance and transparency of the resulting molded article can be further improved.

[0111] As the (meth)acrylate monomer (b2), those exemplified as the (meth)acrylate monomer (a2) are mentioned. As the (meth)acrylate monomer (b2), methyl (meth)acrylate is preferred.

[0112] In the total 100% by mass of the vinyl monomer mixture (mb), the content of the (meth) acrylate monomer (b2) in the vinyl monomer mixture (mb) is preferably 30% by mass or more, more preferably 50% by mass or more. If the content of the (meth) acrylate monomer (b2) is above the above lower limit, the transparency of the obtained molded article can be further improved. In the total 100% by mass of the vinyl monomer mixture (mb), the content of the (meth) acrylate monomer (b2) in the vinyl monomer mixture (mb) is preferably 85% by mass or less, more preferably 75% by mass or less. If the content of the (meth) acrylate monomer (b2) is below the above upper limit, the chemical resistance of the obtained molded article can be further improved.

[0113] Examples of the vinyl cyanide monomer (b3) include those exemplified as the vinyl cyanide monomer (a3). As the vinyl cyanide monomer (b3), acrylonitrile is preferred.

[0114] In the total 100 mass % of the vinyl monomer mixture (mb), the content of the cyanide vinyl monomer (b3) in the vinyl monomer mixture (mb) is preferably 2 to 30 mass %. If the content of the cyanide vinyl monomer (b3) is less than 2 mass %, there is a tendency that the chemical resistance and impact resistance of the obtained molded product are reduced. Therefore, the content of the cyanide vinyl monomer (b3) is preferably 2 mass % or more, more preferably 5 mass % or more. If the content of the cyanide vinyl monomer (b3) exceeds 30 mass %, there is a tendency that the yellowness (YI) of the obtained molded product increases and the hue decreases. Therefore, the content of the cyanide vinyl monomer unit (b3) is preferably 30 mass % or less, more preferably 20 mass % or less.

[0115] Other monomers that can be copolymerized with them are not particularly limited as long as they are vinyl monomers other than the above-mentioned aromatic vinyl monomer (b1), (meth) acrylate monomer (b2) and cyanide vinyl monomer (b3) and do not impair the effect of the present invention. Specifically, substances exemplified as other monomers in the vinyl monomer mixture (ma1) can be cited. When the vinyl monomer mixture (mb) contains these other monomers, its content is preferably 10% by mass or less, more preferably 0 to 5% by mass.

[0116] The weight average molecular weight (Mw) of the acetone soluble component of the rubber reinforced graft copolymer (B) is preferably 30,000 to 500,000, more preferably 40,000 to 250,000, and further preferably 50,000 to 150,000. The rubber reinforced graft copolymer (B) having a weight average molecular weight of 30,000 to 500,000 can be easily produced, for example, by using an initiator and a chain transfer agent described later, and by setting the polymerization temperature to a preferred range described later.

[0117] The graft ratio of the rubber-reinforced graft copolymer (B) is not particularly limited, but is preferably 10 to 150%, more preferably 40 to 120%, from the viewpoint of further improving the impact resistance of the obtained molded article.

[0118] The volume average particle size of the rubber-reinforced graft copolymer (B) is preferably 80 to 500 nm, particularly preferably 100 to 300 nm, from the viewpoint of transparency.

[0119] The refractive index of the acetone soluble component of the rubber reinforced graft copolymer (B) is preferably 1.505 to 1.520, more preferably 1.509 to 1.519, and further preferably 1.510 to 1.517. When the refractive index of the acetone soluble component of the rubber reinforced graft copolymer (B) is within the above range, a rubber reinforced graft copolymer (B) having excellent transparency can be obtained.

[0120] As described above, from the perspective of transparency of the resulting molded article, the refractive index difference between the acetone-soluble components of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C) described below is preferably 0.03 or less, particularly preferably 0.01 or less.

[0121] The grafting ratio of the graft copolymer (B) and the refractive index of the acetone-soluble component were measured by the methods described in the section of Examples described later.

[0122] In the present invention, the difference in refractive index between the acetone soluble component as the graft component of the rubber reinforced graft copolymer (B) and the rubber polymer (r) is preferably 0.03 or less, more preferably 0.01 or less. By making the difference in refractive index between the rubber reinforced graft copolymer (B) and the graft component and the rubber polymer (r) 0.03 or less, the transparency of the obtained molded article can be improved.

[0123] The refractive index of the graft component of the rubber reinforced graft copolymer (B) mainly depends on the composition of the vinyl monomer as a raw material. Therefore, by appropriately selecting the type and composition ratio of the vinyl monomer mixture (mb), the refractive index can be within a desired range. In particular, when the polymerization conversion rate is 95% or more by emulsion polymerization, the composition of the graft component is substantially the same as that of the vinyl monomer mixture (mb).

[0124] The refractive index of the rubber polymer (r) is shown in general literature, and for example, in the case of polybutadiene rubber, it is 1.516.

[0125] The refractive index of the graft component of the graft copolymer (B) can be measured in the same manner as the vinyl copolymer (A) by dissolving the graft copolymer (B) in acetone, filtering the acetone-soluble component, and drying the residue.

[0126] In the present invention, the method for producing the graft copolymer (B) is not particularly limited, and any method such as emulsion polymerization, suspension polymerization, continuous bulk polymerization, solution continuous polymerization, etc. can be used. Among them, emulsion polymerization or bulk polymerization is preferred, and emulsion polymerization is more preferred. If the emulsion polymerization method is used, the particle size of the rubber polymer (r) can be easily adjusted to a desired range, and the polymerization stability can be easily adjusted by removing heat during polymerization.

[0127] In the case of manufacturing the graft copolymer (B) by emulsion polymerization, the method of injecting the rubber polymer (r) and the vinyl monomer mixture (mb) is not particularly limited. For example, they can all be injected at the initial stage. In addition, in order to adjust the distribution of the copolymer composition, a part of the vinyl monomer mixture (mb) can be continuously injected, and a part or all of the vinyl monomer mixture (mb) can also be injected separately. Here, continuously injecting a part of the vinyl monomer mixture (mb) means that a part of the vinyl monomer mixture (mb) is injected at the initial stage, and the remaining part is continuously injected over time. The injection of a part or all of the vinyl monomer mixture (mb) in batches means that a part or all of the vinyl monomer mixture (mb) is injected at the moment after the initial injection.

[0128] In the present invention, the rubber-reinforced graft copolymer (B) may be used alone or as a mixture of two or more kinds of rubber polymers (r) that differ in type, vinyl monomer composition, physical properties, etc.

[0129] <Polyamide elastomer (C)>

[0130] As the polyamide elastomer (C) constituting the thermoplastic resin composition of the present invention, for example, a graft copolymer or block copolymer of an aminocarboxylic acid or lactam having at least 6 carbon atoms, or a salt of a diamine having at least 6 carbon atoms and a dicarboxylic acid and a poly(alkylene oxide) glycol is preferred. As the poly(alkylene oxide) glycol, polyethylene oxide glycol is preferably used.

[0131] Specific examples of the salt of an aminocarboxylic acid or lactam having 6 or more carbon atoms, or a diamine having 6 or more carbon atoms and a dicarboxylic acid include aminocarboxylic acids such as ω-aminocaproic acid, ω-aminoheptanoic acid, ω-aminooctanoic acid, ω-aminononanoic acid, ω-aminodecanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid; lactams such as caprolactam, enantholactam, capryllactam, and laurolactam; nylon salts such as hexamethylenediamine-adipate salt, hexamethylenediamine-sebacate salt, and hexamethylenediamine-isophthalate salt, etc. Two or more of these may be used.

[0132] Examples of poly(alkylene oxide) glycols include polyethylene oxide glycol, poly(1,2-propylene oxide) glycol, poly(1,3-propylene oxide) glycol, poly(butylene oxide) glycol, poly(hexylene oxide) glycol, block copolymers or random copolymers of ethylene oxide and propylene oxide, block copolymers or random copolymers of ethylene oxide and tetrahydrofuran, etc. Two or more of these may be used. Furthermore, bisphenol A, alkylene oxide adducts of fatty acids, etc. may be copolymerized.

[0133] From the viewpoint of improving the mechanical properties of the polyamide elastomer (C), the number average molecular weight of the poly(alkylene oxide) glycol is preferably 200 or more, more preferably 300 or more. From the viewpoint of further improving chemical resistance, the number average molecular weight of the poly(alkylene oxide) glycol is preferably 6,000 or less, more preferably 4,000 or less.

[0134] Both terminals of the poly(alkylene oxide) glycol may be amino or carboxylated as necessary.

[0135] In the present invention, the bond between the aminocarboxylic acid or lactam having 6 or more carbon atoms, or the salt of a diamine having 6 or more carbon atoms and a dicarboxylic acid and the poly(oxyalkylene) glycol is usually an ester bond or an amide bond, but is not particularly limited thereto.

[0136] A third component such as a dicarboxylic acid or a diamine may be used as a reaction component. As a specific example, terephthalic acid (dicarboxylic acid) is added in order to bond nylon 6 to polyethylene glycol.

[0137] When a third component such as a dicarboxylic acid or a diamine is used as a reaction component, a dicarboxylic acid having 4 to 20 carbon atoms is preferred from the viewpoint of further improving polymerizability, color tone and physical properties. Examples thereof include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene-2,7-dicarboxylic acid, diphenyl-4,4-dicarboxylic acid, diphenoxyethanedicarboxylic acid, and sodium 3-sulfoisophthalate; alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, and dicyclohexyl-4,4-dicarboxylic acid; and aliphatic dicarboxylic acids such as succinic acid, oxalic acid, adipic acid, sebacic acid, and 1,10-decanedicarboxylic acid.

[0138] As the diamine, aromatic, alicyclic and aliphatic diamines are used, among which hexamethylenediamine which is an aliphatic diamine is preferably used.

[0139] The method for producing the polyamide elastomer (C) is not particularly limited, and a known production method can be used. For example, in the case of a graft copolymer or a block copolymer containing a poly(alkylene oxide) glycol as a constituent component, the following methods (1) to (3) can be used.

[0140] (1) A method in which (i) a salt of an aminocarboxylic acid or a lactam or a diamine having 6 or more carbon atoms and a dicarboxylic acid is reacted with (ii) a dicarboxylic acid to obtain a polyamide prepolymer having carboxylic acid groups at both ends, and the prepolymer is reacted with (iii) a poly(alkylene oxide) glycol under vacuum;

[0141] (2) A method in which the compounds of (i), (ii) and (iii) are placed in a reaction tank, heated at a high temperature in the presence or absence of water to produce a carboxylic acid-terminated polyamide elastomer, and then polymerized under normal pressure or reduced pressure;

[0142] (3) A method in which the compounds of (i), (ii) and (iii) are simultaneously charged into a reaction vessel, melt polymerized, and then polymerized at once under a high vacuum.

[0143] From the viewpoint of sheet moldability, the melting point of the polyamide elastomer (C) is preferably 140° C. or higher, more preferably 180° C. or higher, and further preferably 190° C. or higher. The upper limit of the melting point of the polyamide elastomer (C) is not particularly limited, but is usually 220° C. or lower.

[0144] The refractive index of the polyamide elastomer (C) is preferably 1.505 to 1.520, more preferably 1.509 to 1.519, and even more preferably 1.510 to 1.517. When the refractive index of the polyamide elastomer (C) is within the above range, the refractive index difference with the rubber-reinforced graft copolymer (B) can be reduced, which is preferred from the perspective of transparency of the obtained molded article.

[0145] As described above, from the perspective of the transparency of the resulting molded article, the difference between the refractive index of the vinyl copolymer (A), the refractive index of the acetone-soluble component of the rubber-reinforced graft copolymer (B), and the refractive index of the polyamide elastomer (C) is preferably 0.03 or less, particularly preferably 0.01 or less.

[0146] The melting point of the polyamide elastomer (C) is measured by the method described in the section of Examples described below. The refractive index of the polyamide elastomer (C) is measured by the method described in the section of Examples described below. However, for commercially available products, the catalog value can be used.

[0147] In the present invention, the polyamide elastomer (C) may be used alone or in combination of two or more types having different segment compositions, physical properties, etc.

[0148] For example, a nylon 6-based polyamide elastomer and a nylon 12-based polyamide elastomer may be used in combination, or polyamide elastomers having different melting points may be used in combination.

[0149] A commercially available product may be used as the polyamide elastomer (C). Examples of commercially available products of the polyamide elastomer (C) include Pelestat M-140, Pelestat NC6321, Pelestat M-330, Pelestat N1200, and Plectron AS manufactured by Sanyo Chemical Co., Ltd.

[0150] <Mixing ratio>

[0151] The thermoplastic resin composition of the present invention is a thermoplastic resin composition comprising 60 to 92 parts by mass of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) and 8 to 40 parts by mass of the polyamide elastomer (C), based on 100 parts by mass of the total of the vinyl copolymer (A) (the vinyl copolymer (A) may be the vinyl copolymer (A1) alone or may be composed of the vinyl copolymer (A1) and the vinyl copolymer (A2)), the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C) (hereinafter, sometimes referred to as "the total of (A) to (C)").

[0152] (Ratio of vinyl copolymer (A) to rubber-reinforced graft copolymer (B))

[0153] In the thermoplastic resin composition of the present invention, in the total of 100 mass % of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B), the proportion of the vinyl copolymer (A) is preferably 20 to 80 mass %, more preferably 25 to 75 mass %, and further preferably 30 to 70 mass %. The proportion of the other rubber-reinforced graft copolymer (B) is preferably 20 to 80 mass %, more preferably 25 to 75 mass %, and further preferably 30 to 70 mass %.

[0154] This is because when the content ratio of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) is within the above range, excellent chemical resistance and transparency are achieved.

[0155] (Content ratio of the total of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) to the polyamide elastomer (C))

[0156] The thermoplastic resin composition of the present invention contains 60 to 92 parts by mass of the vinyl copolymer (A) and the rubber-reinforced graft copolymer (B) in total and 8 to 40 parts by mass of the polyamide elastomer (C) in total of 100 parts by mass of (A) to (C).

[0157] The blending ratio can be appropriately adjusted according to the purpose within the above range.

[0158] (Rubber content in thermoplastic resin composition)

[0159] The content of the rubber polymer (r) in 100% by mass of the thermoplastic resin composition of the present invention (hereinafter sometimes referred to as "rubber content") is preferably 8 to 35% by mass, more preferably 10 to 30% by mass. The lower limit of the content of the rubber polymer (r) is more preferably 11% by mass or more, particularly preferably 12% by mass or more, and most preferably 13% by mass or more. The upper limit of the content of the rubber polymer (r) is more preferably 28% by mass or less, particularly preferably 25% by mass or less, and most preferably 23% by mass or less.

[0160] When the content of the rubber polymer (r) in the thermoplastic resin composition is within the above range, the composition will be excellent in chemical resistance, transparency, and sheet appearance.

[0161] The rubber content in the thermoplastic resin composition can be determined by a method of calculating the content of the rubber polymer (r) in the rubber-reinforced graft copolymer (B) from the blending ratio or by measuring the rubber content using an infrared spectrometer.

[0162] (Content of Vinyl Cyanide Monomer in Acetone Soluble Component of Thermoplastic Resin Composition)

[0163] The content of the cyanide vinyl monomer component in 100% by mass of the acetone soluble component of the thermoplastic resin composition is preferably 0.5 to 10% by mass. If the content of the cyanide vinyl monomer component is less than 0.5% by mass, the dispersibility deteriorates during mixing with the polyamide elastomer (C), and it is difficult to obtain antistatic properties. The content of the cyanide vinyl monomer component is more preferably 1.0% by mass or more, further preferably 2.0% by mass or more, particularly preferably 3.0% by mass or more, and most preferably 4.0% by mass or more. On the other hand, if the content of the cyanide vinyl monomer component exceeds 10% by mass, the processability and transparency during sheet processing are reduced. The content of the cyanide vinyl monomer component is more preferably 9.0% by mass or less, further preferably 8.0% by mass or less, particularly preferably 7.0% by mass or less, and most preferably 6.5% by mass or less, and more preferably 6.0% by mass or less, 5.5% by mass or less, and 5.0% by mass or less.

[0164] By setting the content of the vinyl cyanide monomer component in 100 mass % of the acetone soluble component of the thermoplastic resin composition to the above range, it is possible to sufficiently exhibit chemical resistance while maintaining transparency in sheet processing with lower shear force than injection molding.

[0165] The content of the vinyl cyanide monomer component in the acetone soluble fraction in the thermoplastic resin composition is measured by using an infrared spectrometer to prepare a calibration curve in advance, extracting the polymer of the acetone soluble fraction and then using a measuring device described in the examples below.

[0166] In addition, in the examples described below, the extraction of the polymer from the acetone-soluble component was performed as follows.

[0167] 2 g of each thermoplastic resin composition obtained in the examples and comparative examples was added to 40 mL of acetone, and after shaking for 2 hours using a shaker at 25° C., the mixture was centrifuged for 60 minutes using a centrifuge (rotation speed: 23,000 rpm) at 5° C. to separate the acetone soluble component and the acetone insoluble component. The obtained acetone soluble component was dropped into methanol to precipitate the polymer component, and then the solid component filtered out was dried for 24 hours using a vacuum dryer, and the dried product was extracted as the polymer component of the acetone soluble component in the thermoplastic resin composition.

[0168] The content of the vinyl cyanide monomer component in the acetone soluble fraction can be determined by the above-mentioned direct extraction measurement method or the method of calculating the content of the vinyl cyanide monomer component in the acetone soluble fraction of each raw material from the blending ratio.

[0169] (Weight Average Molecular Weight of Acetone Soluble Component in Thermoplastic Resin Composition)

[0170] The weight average molecular weight of the acetone soluble component of the thermoplastic resin composition is preferably 60,000 to 280,000. This range is preferred because transparency can be maintained during sheet molding and subsequent processing steps. The weight average molecular weight of the acetone soluble component is more preferably 65,000 to 250,000, further preferably 70,000 to 200,000, and particularly preferably 75,000 to 150,000.

[0171] The weight average molecular weight of the acetone soluble component in the thermoplastic resin composition can be measured as a polystyrene-equivalent value based on GPC. The weight average molecular weight of the acetone soluble component can be measured by a measuring device described in the section of Examples described later after extracting the polymer of the acetone soluble component by the above method.

[0172] (Content of each ingredient)

[0173] The thermoplastic resin composition of the present invention preferably contains 20 to 65 parts by mass of the vinyl copolymer (A), 5 to 72 parts by mass of the rubber-reinforced graft copolymer (B), and 8 to 30 parts by mass of the polyamide elastomer (C) relative to 100 parts by mass of the total of (A) to (C). More preferably, it contains 20 to 60 parts by mass of the vinyl copolymer (A), 15 to 72 parts by mass of the rubber-reinforced graft copolymer (B), and 8 to 25 parts by mass of the polyamide elastomer (C), and further preferably, it contains 20 to 55 parts by mass of the vinyl copolymer (A), 25 to 72 parts by mass of the rubber-reinforced graft copolymer (B), and 8 to 20 parts by mass of the polyamide elastomer (C).

[0174] In addition, the thermoplastic resin composition of the present invention may contain 20 to 40 parts by mass of the vinyl copolymer (A), 47 to 65 parts by mass of the rubber-reinforced graft copolymer (B), and 8 to 13 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of (A) to (C), and may contain 35 parts by mass or less of the vinyl copolymer (A1) in the vinyl copolymer (A).

[0175] When the content of the vinyl copolymer (A) in a total of 100 parts by mass of (A) to (C) is less than the above lower limit, the effect of improving the rigidity and heat resistance of the obtained molded product by containing the vinyl copolymer (A) cannot be fully obtained. If the content of the vinyl copolymer (A) exceeds the above upper limit, the moldability of the sheet is reduced. The more preferred content of the vinyl copolymer (A) in a total of 100 parts by mass of (A) to (C) is as described above.

[0176] From the viewpoint of transparency and rigidity of the obtained molded article, the content of the vinyl copolymer (A1) in the vinyl copolymer (A) is preferably 35 parts by mass or less, more preferably 30% by mass or less, in 100 parts by mass of the total of (A) to (C).

[0177] When the vinyl copolymer (A) comprises a vinyl copolymer (A1) and a vinyl copolymer (A2), the content of the vinyl copolymer (A2) is preferably 20 parts by mass or less, more preferably 5 to 20 parts by mass, and even more preferably 8 to 18 parts by mass relative to 100 parts by mass of the total of (A) to (C), from the perspectives of heat resistance, chemical resistance and sheet formability.

[0178] When the content of the graft copolymer (B) in the total of 100 parts by mass of (A) to (C) is less than the above lower limit, the effect of improving the chemical resistance of the molded product and the fluidity suitable for sheet molding by containing the rubber-reinforced graft copolymer (B) cannot be fully obtained. If the content of the graft copolymer (B) exceeds the above upper limit, the effect of improving the rigidity and heat resistance of the molded product cannot be fully obtained. The more preferred content of the graft copolymer (B) in the total of 100 parts by mass of (A) to (C) is as described above.

[0179] When the content of the polyamide elastomer (C) in the total of 100 parts by mass of (A) to (C) is less than 8 parts by mass, the effect of improving the chemical resistance brought about by the inclusion of the polyamide elastomer (C) cannot be fully obtained, and the chemical resistance of the obtained molded article is reduced. The content of the polyamide elastomer (C) is preferably 8 parts by mass or more, and particularly preferably 10 parts by mass or more. On the other hand, from the aspect of improving the rigidity of the obtained molded article, the content of the polyamide elastomer (C) in the total of 100 parts by mass of (A) to (C) is 40 parts by mass or less, preferably 30 parts by mass or less, more preferably 25 parts by mass or less, further preferably 20 parts by mass or less, particularly preferably 18 parts by mass or less, and particularly preferably 13 parts by mass or less.

[0180] <Other ingredients>

[0181] The thermoplastic resin composition of the present invention may contain resins and elastomers other than the vinyl copolymer (A), the graft copolymer (B) and the polyamide elastomer (C) within the range that the effects of the present invention are not impaired. Examples of these other resins and elastomers include one or more transparent resins such as polycarbonate resins and polymethyl methacrylate.

[0182] When the thermoplastic resin composition of the present invention contains these resins and elastomers, the content thereof is preferably 10 parts by mass or less in 100 parts by mass of the total of the vinyl copolymer (A), the graft copolymer (B), the polyamide elastomer (C), and the other resins and elastomers. If the content is below the above upper limit, the effect of the present invention brought about by using the vinyl copolymer (A), the graft copolymer (B), and the polyamide elastomer (C) in a prescribed ratio can be effectively obtained.

[0183] The thermoplastic resin composition of the present invention may be mixed with the following antioxidants, such as hindered phenol-based, sulfur-containing organic compound-based, phosphorus-containing organic compound-based, etc., heat stabilizers, such as phenol-based, acrylate-based, etc., ultraviolet absorbers, such as benzotriazole-based, benzophenone-based, salicylate-based, etc., various stabilizers, such as organic nickel-based, hindered amine-based, etc., light stabilizers, such as lubricants, such as metal salts of higher fatty acids, higher fatty acid amides, etc., plasticizers, such as phthalates, phosphates, etc., anti-drip agents, such as polytetrafluoroethylene, nonionic, anionic, cationic, or amphoteric surfactants, pigments and dyes, such as carbon black, titanium oxide, etc., and liquids, such as water, silicone oil, and liquid paraffin, etc. In addition, fillers may be mixed.

[0184] As fillers, fillers in the shape of fibers, plates, powders, granules, etc. can be cited, and any one of them can be used in the present invention. Specifically, polyacrylonitrile (PAN)-based or asphalt-based carbon fibers; metal fibers such as stainless steel fibers, aluminum fibers, and brass fibers; organic fibers such as aromatic polyamide fibers; gypsum fibers, ceramic fibers, asbestos fibers, zirconium oxide fibers, aluminum oxide fibers, silica fibers, titanium oxide fibers, silicon carbide fibers, glass fibers, asbestos, potassium titanate whiskers, barium titanate whiskers, aluminum borate whiskers, silicon nitride whiskers, and other fibrous or whisker-like fillers; mica, talc, kaolin, silica, calcium carbonate, glass flakes, glass beads, glass microspheres, clay, molybdenum disulfide, wollastonite, montmorillonite, titanium oxide, zinc oxide, barium sulfate, calcium polyphosphate, graphite, and other powdered, granular, or plate-like fillers; etc. They can be used in two or more kinds. Among them, glass fibers are preferably used. The type of glass fiber is not particularly limited as long as it is glass fiber generally used for reinforcing resins, and examples thereof include long fiber type, short fiber type, chopped strands, milled fibers, and the like.

[0185] The surface of the above-mentioned filling material can be treated with any coupling agent (such as silane coupling agent, titanate coupling agent, etc.) or other surface treatment agent. The above-mentioned filling material can be coated or bundled with thermoplastic resins such as ethylene / vinyl acetate copolymers and thermosetting resins such as epoxy resins. The above-mentioned filling material can be treated with coupling agents such as aminosilane and epoxysilane.

[0186] When the thermoplastic resin composition of the present invention contains a filler, the content thereof is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the total of the vinyl copolymer (A), the graft copolymer (B) and the polyamide elastomer (C). By making the content of the filler within the above range, the rigidity and heat resistance of the obtained molded article can be further improved.

[0187] <Method for producing thermoplastic resin composition>

[0188] The method for producing the thermoplastic resin composition is not particularly limited. The thermoplastic resin composition of the present invention is produced by mixing the vinyl copolymer (A), the graft copolymer (B), the polyamide elastomer (C), and other components used as required in the above-specified ratios.

[0189] From the aspect of productivity, the method of melt-kneading the vinyl copolymer (A), the graft copolymer (B), the polyamide elastomer (C) and other components as required is usually adopted. When the above-mentioned additives are mixed, there is no particular limitation on the mixing method, and various methods can be used.

[0190] <Method for molding thermoplastic resin composition>

[0191] The thermoplastic resin composition of the present invention can be molded by a known method such as injection molding, extrusion molding, calender molding, blow molding, vacuum molding, compression molding, gas-assisted molding, etc.

[0192] <Physical Properties of Thermoplastic Resin Composition>

[0193] From the viewpoint of sheet moldability, the melt volume rate (MVR) of the thermoplastic resin composition of the present invention measured by the method described in the section of Examples described later is preferably 50 cm 3 / 10 minutes or less, more preferably 30cm 3 / 10 minutes or less, more preferably 20cm 3 On the other hand, from the perspective of sheet moldability and sheet appearance, the MVR of the thermoplastic resin composition of the present invention is preferably 2 cm 3 / 10 minutes or more, more preferably 4cm 3 / 10 minutes or more, more preferably 6cm 3 / More than 10 minutes.

[0194] From the viewpoint of transparency, the total light transmittance of the thermoplastic resin composition of the present invention measured by the method described in the section of Examples described later is preferably 85% or more, more preferably 87% or more.

[0195] From the viewpoint of rigidity, the flexural modulus of the thermoplastic resin composition of the present invention measured by the method described in the section of Examples described later is preferably 900 MPa or more, more preferably 1,000 MPa or more.

[0196] From the viewpoint of heat resistance, the heat deformation temperature of the thermoplastic resin composition of the present invention measured by the method described in the section of Examples described later is preferably 58° C. or higher, more preferably 60° C. or higher, and even more preferably 63° C. or higher.

[0197] [Molding products]

[0198] The molded article of the present invention is obtained by molding the thermoplastic resin composition of the present invention by various molding methods as described above. The molded article of the present invention can be applied to a wide range of application fields such as home appliances, communication-related equipment, transport containers, general sundries, and medical-related equipment.

[0199] In particular, the thermoplastic resin composition of the present invention is particularly preferably used as a film or sheet formed by T-die molding or calendaring due to its excellent sheet moldability, chemical resistance, transparency, rigidity, and heat resistance. The molded article of the present invention is particularly preferably used as a conveying device or a transport container for precision parts, in which case, even if a cleaning agent or the like is attached, high transparency can be maintained and cracks and breakages can be prevented.

[0200] The molded article of the present invention can be widely used not only as a product for general use such as a transparent storage box, but also as a component for producing industrial products such as photomasks.

[0201] Example

[0202] The present invention will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples unless the scope of the present invention is exceeded.

[0203] In addition, in the following description, "parts" means "parts by mass" and "%" means "% by mass".

[0204] [Measurement and evaluation methods]

[0205] Various measurement and evaluation methods in the following Examples and Comparative Examples are as follows.

[0206] <Volume Average Particle Size>

[0207] It was determined by a dynamic light scattering method using Nanotrac UPA-EX150 manufactured by Nikkiso Co., Ltd.

[0208] <Grafting rate>

[0209] 1 g (W: sample weight) of the graft copolymer (B) was added to 80 mL of acetone and heated under reflux at 65 to 70°C for 3 hours. The resulting suspended acetone solution was centrifuged at 14,000 rpm for 30 minutes using a centrifuge ("CR21E" manufactured by Hitachi Koki Co., Ltd.) to separate the precipitate (acetone insoluble component) and the acetone solution (acetone soluble component). The precipitate (acetone insoluble component) was then dried and its weight (Q (g)) was measured, and the grafting rate was calculated using the following formula (1).

[0210] Q in formula (1) is the weight (g) of the acetone insoluble component of the graft copolymer (B). W is the total weight (g) of the graft copolymer (B) used to calculate Q. The rubber fraction is the content of the rubber polymer (r) contained in the graft copolymer (B).

[0211] Grafting rate (%) = {(Q - W × rubber fraction) / W × rubber fraction} × 100 ... (1)

[0212] <Polymerization Conversion Rate>

[0213] 1 g of the latex of the graft copolymer (B) was collected and accurately weighed, and dried in a hot air dryer at 150°C for 1 hour. The weight after drying was accurately weighed as the solid content. Next, the ratio of the accurate weighing results before and after drying was calculated as the solid content ratio in the latex. Finally, the polymerization conversion rate was calculated using the solid content ratio according to the following formula (2).

[0214] Polymerization conversion rate (%) = (total weight of input raw materials × solid content ratio - total weight of raw materials other than monomers) / weight of input monomers × 100 ... (2)

[0215] <Infrared Spectroscopy Analysis>

[0216] The following (1) and (2) were measured using a Fourier transform infrared spectrophotometer FT-IR "FT-720" manufactured by Horiba, Ltd.

[0217] (1) Content of vinyl cyanide monomer component in acetone soluble fraction (represented as "AN content" in Tables 1 to 3)

[0218] (2) Ratio of polymer compositions of the produced vinyl copolymer (A) and rubber-reinforced graft copolymer (B)

[0219] <Weight average molecular weight (Mw)>

[0220] The weight average molecular weight (Mw) in terms of polystyrene was measured using GPC (GPC: "GPC / V2000" manufactured by Waters, column: "Shodex AT-G+AT-806MS" manufactured by Showa Denko K.K.).

[0221] <Refractive Index>

[0222] The measurement was performed at 23°C using an Abbe refractometer "KPR-30A" manufactured by Shimadzu Corporation.

[0223] The refractive index of each copolymer was measured by precipitating and recovering the copolymer from an aqueous dispersion of the vinyl copolymer (A1) or the graft copolymer (B) with isopropyl alcohol, and measuring the refractive index of the dried product.

[0224] <Glass transition temperature>

[0225] The glass transition temperature (Tg) of the vinyl copolymer (A-2-1) was measured by differential scanning calorimetry (DSC) and was the glass transition temperature observed when a sample was heated from 35°C to 250°C at 10°C / min in a nitrogen atmosphere, then cooled to 35°C and then heated again to 250°C.

[0226] <Melting point (Tm)>

[0227] In accordance with JIS K 7121-1987, DSC (differential scanning calorimeter) was used to measure endothermic changes at a constant temperature increase rate of 20° C. per minute, and the peak temperature of the endothermic pattern obtained was defined as the melting point (Tm).

[0228] <Liquidity (MVR)>

[0229] The MVR of the thermoplastic resin composition obtained by melt kneading was measured at 220° C. and 10 kgf in accordance with ISO 1133. The MVR serves as a criterion for the fluidity of the thermoplastic resin composition.

[0230] <Total light transmittance>

[0231] The measurement was performed in accordance with ASTM 1003. The thickness of the test piece was 2.5 mm.

[0232] In addition, the following evaluation was performed as environmental impact.

[0233] After measuring the total light transmittance of the test piece, place the test piece in a constant temperature and high humidity tank at 40°C and 70% humidity for one week. Then, take out the test piece and measure the total light transmittance again. Confirm the difference between the total light transmittance before and after the constant temperature and high humidity tank, and judge according to the following grades. The smaller the difference, the smaller the environmental impact, and A is the most excellent.

[0234] A: Less than 1%

[0235] B: More than 1% and less than 3%

[0236] C: More than 3% and less than 5%

[0237] D: more than 5%

[0238] <Sheet molding>

[0239] Each resin composition was extruded into a resin sheet of 220 mm (width)×320 mm (length)×1 mm (thickness).

[0240] (Evaluation-1: Film appearance)

[0241] The appearance of the resin sheet was visually observed and judged based on the following criteria. In the judgment, A was excellent.

[0242] A: Good (no problem)

[0243] B: Slightly visible defect (can be used depending on the application)

[0244] C: Large area with small defects (can be used for quite limited purposes)

[0245] D: Defective (cannot be used as a product)

[0246] (Evaluation-2: Readability: 2D barcode)

[0247] Use a two-dimensional barcode (size 13×13mm) and a smartphone, make them face to face and fix them at an interval of 130mm. Insert a resin sheet in between, move the resin sheet from the smartphone side to the two-dimensional barcode side, and measure the distance from the two-dimensional barcode to the resin sheet when the smartphone reads the two-dimensional barcode. The larger the distance, the easier it is to see the image information of the two-dimensional barcode, and the better. It should be noted that ND means cannot be read.

[0248] This evaluation is an evaluation based on the assumption that the sheet can be read from an external camera in a state where the sheet is regarded as a product (transparent case) and the components with two-dimensional bar codes are stored therein.

[0249] <Flexural modulus (rigidity)>

[0250] The measurement was performed in accordance with ISO178.

[0251] <Chemical resistance (bending method)>

[0252] Using an injection molding machine ("IS55FP-1.5A" manufactured by Toshiba Machine Co., Ltd.), a test piece was molded from a granular thermoplastic resin composition using an ESC mold (thickness 2 mm, width 12 mm, length 15 mm). The test piece was mounted on a fixed strain fixture with a strain rate of 0.2 to 1.6%, and isopropyl alcohol (Wako Pure Chemical Industries, Ltd.) was dripped on it. Then, after being placed in an atmosphere of 23°C and 50% RH for 48 hours, the test piece was removed from the fixture and the critical strain (%) of the material that produced degradation and cracking was determined. The larger the critical strain (%), the better the chemical resistance.

[0253] <Heat Deformation Temperature (HDT)>

[0254] According to ASTM D648, load 18.56kg / cm 2 The heat distortion temperature (HDT) was measured. The thickness of the test piece was 1 / 2 inch.

[0255] [Manufacturing and preparation of mixed ingredients]

[0256] In the following Examples and Comparative Examples, each component used in the production of the thermoplastic resin composition was produced by the following method. Alternatively, the following commercially available products were used.

[0257] <Production of Vinyl Copolymer (A-1-1)>

[0258] Two stainless steel autoclaves with a volume of 30 liters and equipped with spiral blades were connected and replaced with nitrogen. Then, 21 parts of styrene, 7 parts of acrylonitrile, 72 parts of methyl methacrylate, and 20 parts of toluene were continuously added to the first reaction container. A solution of 0.15 parts of tert-dodecyl mercaptan and 5 parts of toluene as a molecular weight regulator and a solution of 0.1 parts of diisopropylbenzene peroxide and 5 parts of toluene as a polymerization initiator were continuously supplied. The polymerization temperature of the first reactor was controlled at 110°C, and the average residence time was 2.0 hours. The obtained polymer solution was continuously taken out by a pump provided outside the first reactor in an amount equal to the supply amount of styrene, acrylonitrile, methyl methacrylate, toluene, molecular weight regulator, and polymerization initiator, and supplied to the second reactor. The polymerization temperature of the second reactor was set to 130°C. The copolymer solution obtained from the second reaction vessel was directly devolatilized from unreacted monomers and solvent using a twin-screw extruder with three-stage vents to obtain a vinyl copolymer (A-1-1).

[0259] The analysis results of the vinyl copolymer (A-1-1) are as follows.

[0260] Weight average molecular weight (Mw): 120,000

[0261] Refractive index: 1.517

[0262] <Production of Vinyl Copolymer (A-1-2)>

[0263] A powdery vinyl copolymer (A-1-2) was obtained in the same manner as in the production of the vinyl copolymer (A-1-1) except that 21 parts of styrene, 13 parts of acrylonitrile, 67 parts of methyl methacrylate, 0.4 parts of tert-dodecyl mercaptan and 0.1 parts of dicumyl peroxide were used.

[0264] The analysis results of the vinyl copolymer (A-1-2) are as follows.

[0265] Weight average molecular weight (Mw): 80,000

[0266] Refractive index: 1.517

[0267] <Production of Vinyl Copolymer (A-1-3)>

[0268] A vinyl copolymer (A-1-3) was obtained in the same manner as in the production of the vinyl copolymer (A-1-1) except that the amount of tert-dodecyl mercaptan used as a molecular weight modifier was changed to 0.27 parts.

[0269] The analysis results of the vinyl copolymer (A-1-3) are as follows.

[0270] Weight average molecular weight (Mw): 85,000

[0271] Refractive index: 1.517

[0272] <Vinyl Copolymer (A-2-1)>

[0273] As the vinyl copolymer (A-2-1), "POLYIMILEX PML203 (refractive index: 1.516)" manufactured by Nippon Shokubai Co., Ltd. was used. The monomer composition (mass ratio) of the vinyl copolymer (A-2-1) was as follows, and the weight average molecular weight (Mw) and glass transition temperature (Tg) were measured, and the results were as follows.

[0274] Monomer composition: methyl methacrylate / N-phenylmaleimide / styrene / =67 / 28 / 5 (mass ratio)

[0275] Weight average molecular weight (Mw): 200,000

[0276] Glass transition temperature (Tg): 140°C

[0277] <Production of Graft Copolymer (B-1)>

[0278] Into a separable flask with an internal volume of 10 L equipped with a stirrer, 45 parts of latex (r-1) (solid content concentration 50%) containing polybutadiene rubber having a volume average particle size of 280 nm and a gel content of 90% were placed, and then 0.5 parts of potassium oleate, 0.2 parts of glucose, 0.2 parts of sodium pyrophosphate, 0.01 parts of ferrous sulfate and 100 parts of deionized water were added. Next, the mixture was heated under stirring, and a monomer mixture consisting of 39.1 parts of methyl methacrylate, 12.7 parts of styrene, 3.2 parts of acrylonitrile, 0.4 parts of diisopropylbenzene hydroperoxide and 0.8 parts of tert-dodecyl mercaptan was continuously added over 5 hours to polymerize at 70°C. The obtained latex was coagulated, washed with water and dried to obtain a powdery graft copolymer (B-1) containing fine particles consisting of grafted polybutadiene and free methyl methacrylate, styrene and acrylonitrile copolymer (polymerization conversion 98%).

[0279] The grafted polybutadiene (acetone insoluble component) obtained by acetone treatment of the graft copolymer (B-1) had a grafting rate of 52% and a volume average particle size of 260 nm. In addition, the free methyl methacrylate·styrene·acrylonitrile copolymer (acetone soluble component) had a refractive index of 1.517 and a weight average molecular weight of 54,000.

[0280] <Polyamide elastomer (C)>

[0281] The polyamide elastomer (C) used was "Pelestat M-140 (refractive index: 1.510)" manufactured by Sanyo Chemical Co., Ltd., which is a nylon 6-based polyetheresteramide block polymer. The melting point of the polyamide elastomer (C) was measured, and the results are as follows.

[0282] Melting point: 192°C

[0283] <Lubricant (D-1)>

[0284] As the lubricant (D-1), "ALFLOW H50S" manufactured by NOF Corporation was used.

[0285] <Compatibilizer (E-1)>

[0286] As the compatibilizer (E-1), an acrylonitrile / α-methylstyrene / acrylic acid copolymer (acrylonitrile / α-methylstyrene / acrylic acid=20 / 75 / 5 (mass ratio)), weight average molecular weight: 67,000) was used.

[0287] <Other ingredients>

[0288] Polyamide: "AMILAN CM1017" manufactured by Toray Industries, Inc.

[0289] Polyethylene glycol: "PEG6000S" manufactured by Sanyo Chemical Industries, Ltd.

[0290] [Examples 1 to 24, Comparative Examples 1 to 8]

[0291] The components shown in Tables 1 to 3 were mixed in the amounts shown in Tables 1 to 3, and 0.00005 parts of solvent blue 97 was further mixed as a dye, and the mixture was mixed at 23° C. using a Henschel mixer. The twin-screw extruder melt-kneaded the mixture at an extrusion temperature of 230° C., extruded the mixture into strands, and pelletized the strands. The obtained pellets of the thermoplastic resin composition were used to perform evaluations according to the above-mentioned method. The results are shown in Tables 1 to 3.

[0292] [Table 1]

[0293]

[0294] [Table 2]

[0295]

[0296] [Table 3]

[0297]

[0298] The following can be seen from Tables 1 to 3.

[0299] In Comparative Examples 1, 2, and 4 not containing the polyamide elastomer (C), the chemical resistance was significantly deteriorated.

[0300] In Comparative Example 3, in which the polyamide elastomer (C) was contained but the compounding amount thereof was small, the chemical resistance was poor.

[0301] In Comparative Example 5, in which polyamide was used as a hard segment of the polyamide elastomer (C) instead of the polyamide elastomer (C), the transparency was poor and the sheet appearance and readability were also poor.

[0302] Comparative Example 6, in which polyethylene glycol was used as a soft segment of the polyamide elastomer (C) instead of the polyamide elastomer (C), had a tendency to have low fluidity (sheet moldability) and was extremely poor in transparency, sheet appearance, readability, and heat resistance.

[0303] In Comparative Example 7 which did not contain the vinyl copolymer (A1) component, the value of flowability was too low, moldability was poor, and transparency, sheet appearance, and readability were also poor.

[0304] In Comparative Example 8 in which the polyamide elastomer (C) was excessively compounded, the transparency, sheet appearance, and readability were poor, the rigidity was low, and the chemical resistance was also poor.

[0305] The disadvantages of the compositions shown in these comparative examples are not at a level that can be adjusted by setting conditions for molding processing and the like, and therefore are not practical.

[0306] On the other hand, the thermoplastic resin compositions of Examples 1 to 24 satisfying the requirements of the present invention are well-balanced in all aspects of low fluidity (sheet moldability), transparency, sheet appearance, readability, impact resistance, chemical resistance, and heat resistance.

[0307] Although polyamide elastomer (C) is sufficiently contained, Example 7, which contains a large amount of graft copolymer (B), has slightly poorer heat resistance than other examples. Example 8, which contains a large amount of vinyl copolymer (A1), tends to have poor sheet moldability, but they are all at a practical level.

[0308] Although Example 9 containing a large amount of the polyamide elastomer (C) tends to have lower rigidity than other examples, it can be used depending on the application.

[0309] In Example 10 using the vinyl copolymer (A-1-2) having a weight average molecular weight of 80,000, the copolymer tends to have low fluidity (sheet moldability) and poor chemical resistance, but can be used.

[0310] In Examples 11 to 24, low fluidity (sheet moldability), transparency, impact resistance, chemical resistance, and heat resistance are all well balanced. Moreover, the environmental impact of the total light transmittance is small, the sheet appearance is excellent, and the readability (distance) is also excellent. Therefore, it can also be used for applications such as photomask boxes.

[0311] It should be noted that the polyamide elastomer (C) can also be expected to have an antistatic effect. For example, the pellets of the thermoplastic resin composition of Example 23 were molded, and the resulting disc (diameter 100 mm, thickness 2 mm) was placed under the conditions of temperature 23°C and humidity 50% RH for 1 day, and the surface resistivity (Ω) was measured under an applied voltage of 500 V. The result showed that 5×10 10 Good value.

[0312] Although the present invention has been described in detail using specific embodiments, it is apparent to those skilled in the art that various modifications can be made within the scope of the invention.

[0313] This application is based on Japanese patent application No. 2022-148261 filed on September 16, 2022, the entirety of which is incorporated herein by reference.

Claims

1. A thermoplastic resin composition, comprising: A vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2); A rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r); and Polyamide elastomer (C), in, The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 50,000 to 300,000. The thermoplastic resin composition contains a total of 60 to 92 parts by mass of the vinyl copolymer (A) and the rubber reinforced graft copolymer (B), and 8 to 40 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B) and the polyamide elastomer (C).

2. The thermoplastic resin composition according to claim 1, wherein The composition comprises 20 to 65 parts by mass of the vinyl copolymer (A), 5 to 72 parts by mass of the rubber reinforced graft copolymer (B) and 8 to 30 parts by mass of the polyamide elastomer (C), based on 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B) and the polyamide elastomer (C).

3. The thermoplastic resin composition according to claim 1, comprising: A vinyl copolymer (A) obtained by copolymerizing a vinyl monomer mixture (ma) containing an aromatic vinyl monomer (a1) and a (meth)acrylate monomer (a2); A rubber-reinforced graft copolymer (B) obtained by graft-copolymerizing a vinyl monomer mixture (mb) containing at least an aromatic vinyl monomer (b1), a (meth)acrylate monomer (b2) and a cyanide vinyl monomer (b3) in the presence of a rubber polymer (r); and Polyamide elastomer (C), in, The vinyl copolymer (A) comprises a vinyl copolymer (A1) obtained by copolymerizing a vinyl monomer mixture (ma1) containing an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a cyanide vinyl monomer (a3), and has a weight average molecular weight of 100,000 to 250,000. The thermoplastic resin composition contains 20 to 40 parts by mass of the vinyl copolymer (A), 47 to 65 parts by mass of the rubber reinforced graft copolymer (B), and 8 to 13 parts by mass of the polyamide elastomer (C), relative to 100 parts by mass of the total of the vinyl copolymer (A), the rubber reinforced graft copolymer (B), and the polyamide elastomer (C), and contains 35 parts by mass or less of the vinyl copolymer (A1).

4. The thermoplastic resin composition according to claim 1, wherein The vinyl copolymer (A) further comprises a vinyl copolymer (A2), which is obtained by copolymerizing a vinyl monomer mixture (ma2) comprising an aromatic vinyl monomer (a1), a (meth)acrylate monomer (a2) and a maleimide monomer (a4), and has a weight average molecular weight of 100,000 to 250,000. The thermoplastic resin composition contains 20 parts by mass or less of the vinyl copolymer (A2) based on 100 parts by mass of the total of the vinyl copolymer (A), the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C).

5. The thermoplastic resin composition according to claim 1, wherein The refractive index of the vinyl copolymer (A), the acetone soluble component of the rubber-reinforced graft copolymer (B) and the polyamide elastomer (C) is in the range of 1.505 to 1.

520. The difference in refractive index between these components is 0.03 or less.

6. The thermoplastic resin composition according to claim 1, wherein The content of the vinyl cyanide monomer component in 100% by mass of the acetone-soluble component of the thermoplastic resin composition is 0.5 to 10% by mass. 7 . A molded article comprising the thermoplastic resin composition according to claim 1 . The molded article according to claim 7 , which is a sheet-shaped molded article.

Citation Information

Patent Citations

  • Production of rubber-modified copolymer resin and rubber-modified copolymer resin composition

    JP1992180907A

  • Transparence-durable antistatic thermoplastic resin composition having excellent impact resistance

    JP2003147152A

  • Thermoplastic resin composition, method for producing the same, and molded product

    JP2017145365A

  • Article recovery system, article recovery robot, article recovery method, and article recovery program

    JP2022148261A

  • Thermoplastic resin composition, method for producing same, and molded article of same

    WO2016104259A1